“We are all Treaty People”: Assessing the Gap between the Dream and the Reality of Treaty-Based Governance in Saskatchewan - Dubois, Janique (Nouvelles pratiques sociales, 2014)
In 1996, the Federation of Saskatchewan Indian Nations, the Government of Canada and the Government of Saskatchewan embarked on an ambitious project: they wanted to abandon the colonial legacy of the Indian Act and instead develop a governance framework based on partnerships between self-determining nations. Grounding negotiations in treaties, this “made in Saskatchewan” solution proposed to develop a province-wide system of First Nation governance representing over 115,000 members and seventy communities. Despite efforts to build a novel treaty-based governance framework, negotiations eventually failed. In assessing the gap between the dream and the reality of treaty-based governance in Saskatchewan, this article argues that the failure of the “made in Saskatchewan” solution lies in the parties’ inability to break away from Canada’s colonial path and fully embrace the reality that “we are all treaty people.”